Media tone: The role of news and social media on heterogeneous inflation expectations - Joni Heikkinen; Kari Heimonen (Bank of Finland, 2024)
This study investigates the role of media tone on inflation expectations. Examining the relationships between news and the inflation expectations of various U.S demographic groupings, we find that traditional news influences older cohorts, while social media news align more closely with the expectations of younger and more educated groups. Interestingly, social media correspond more closely than traditional news with the expectations of professional forecasters. Our analysis shows that media influences can persist for longer than a year, highlighting the importance of historical inflation data and the gradual adaptation of new information. Additionally, we find that separate media tones for specific news topics such as "Inflation & Fed" and "Healthcare Costs" resonate differently across demographic groups. These insights highlight the nuanced role of media in shaping inflation expectations across demographic segments.
urn:nbn:fi-fe2024090569406
Keywords: E3; E31; E32; E52; E58; 330; Inflation Expectations; Household Heterogeneity; Media Tone; Local Projection; Language Model; Forecasting